From Code-To-Cure: Harnessing Immunoinformatics for Next-Gen Vaccine Development - Ananyaa Srivastava; Deepa Singh; Jeevan Patra (Asian Journal of Pharmaceutical Research and Development, 2025)
Vaccination is an important intervention in preventing infectious disease epidemics, saving millions of lives, and reducing infection rates.Vaccines have helped treat various illnesses for years by reducing or eliminating disease burdens. World Health Organization asserts that three million people are saved yearly because of immunization. The new direction in the development of vaccines currently is multi-epitope-based peptide vaccines. Epitope-based peptide vaccines are short protein fragments, known as epitopes, that induce an immune response against a particular pathogen. The conventional approach in vaccine design is labor-intensive, expensive, and time-consuming. The advances in immunoinformatics and vaccinomics have remodeled the face of vaccine science to next-generation vaccine design. Now, virtually new constructs of vaccines can be developed by knowledge of Reverse Vaccinology, various repositories of vaccines, and throughput methods. Such in silico vaccine research tools are strong, inexpensive, accurate, and safe for humans. The candidates for vaccines have rapidly moved into the stage of clinical trials already over the past more than a timeline.The present article will provide detailed information on immunoinformatics working protocol, available databases,and applications of in silico vaccine design with recent case studies that will assist researchers in further tailoring vaccines more rapidly and cost-effectively.